Front Cover: Synthesis and Structure−Activity Relationships of Imidazopyridine/Pyrimidine‐ and Furopyridine‐Based Anti‐infective Agents against Trypanosomiases (6/2021). (19th March 2021) - G. Silva, Daniel; Junker, Anna; M. G. de Melo, Shaiani; Fumagalli, Fernando; Robert Gillespie, J.; Molasky, Nora; S. Buckner, Frederick; Matheeussen, An; Caljon, Guy; Maes, Louis; S. Emery, Flavio
Abstract : The Front Cover shows efforts among Brazilian, American, and European researchers to combat neglected tropical diseases. New heterocyclic compounds based on imidazopyridine/pyrimidine and furopyridine cores originating from Brazil travel to the USA and Europe to be developed as anti‐infective agents against Trypanosomiases. By exploring the chemical diversity at eight different positions of the central core, we obtained various heterocyclic compounds having significant potential for anti‐trypanosomiases drug discovery. More information can be found in the Full Paper by Daniel G. Silva, Flavio S. Emery et al . Cover design by Daniel Gedder Silva.